Reconstructing Our Orders Artificial Intelligence and Human Society (Springer Singapore, 2018)
This book discusses in detail the great historical and social significance of the development of Artificial Intelligence (AI). It consists of seven chapters, each focusing on a specific issue related to AI, such as ethical principles, legal regulations, education, employment and security. Adopting a multidisciplinary approach, it appeals to wide readership, ranging from experts and government officials to the general public.